2023
DOI: 10.31557/apjcp.2023.24.5.1759
|View full text |Cite
|
Sign up to set email alerts
|

Survival after Diagnosis of Cervical Cancer Patients at a Tertiary Referral Hospital in Northeast Thailand

Abstract: Background: Cervical cancer (CC) is the third most common cancer in women globally, including Thailand, where the incidence rate was 16.2 cases per 100,000 individuals in 2018. Survival rates for patients with this condition have not improved over recent years. This study evaluated the survival rate and median survival time after diagnosis among CC patients, and investigated factors associated with survival in Northeast Thailand. Methods: This study included CC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…These results are consistent with previous studies from Thailand, which have consistently shown that CCA incidence is higher in males than females, with the majority of cases occurring in individuals over 60 years old [ 31 , 27 , 20 ]. Furthermore, earlier studies conducted in Thailand in 2021 and 2023 also reported an association between higher rates of CCA and male gender and the age group over 60 years [ 32 , 16 ]. This association has been reported in various studies conducted in different years, emphasizing the importance of monitoring these specific risk factors in CCA incidence.…”
Section: Discussionmentioning
confidence: 96%
“…These results are consistent with previous studies from Thailand, which have consistently shown that CCA incidence is higher in males than females, with the majority of cases occurring in individuals over 60 years old [ 31 , 27 , 20 ]. Furthermore, earlier studies conducted in Thailand in 2021 and 2023 also reported an association between higher rates of CCA and male gender and the age group over 60 years [ 32 , 16 ]. This association has been reported in various studies conducted in different years, emphasizing the importance of monitoring these specific risk factors in CCA incidence.…”
Section: Discussionmentioning
confidence: 96%
“…All tests were two-sided, with statistical significance set at a p-value less than 0.05. STATA version 18 (StataCorp, College Station, TX) was utilized for all analyses [ 19 ].…”
Section: Methodsmentioning
confidence: 99%